Prediction of SAR and temperature distribution in the human ear and mouth exposed to handheld transmitters - ÇALLIALP, FULYA (TAYLOR & FRANCIS LTD, 2018)
As the body centric communication technology develops in monitoring real-time healthcare, fitness, sports, and military, significant attention arises in regarding possible health risks. The aim of this study is to evaluate radio frequency exposure level of various types of wearable devices in terms of the available international recommendations. Specific absorption rate and maximum temperature increase are studied in the human ear and mouth when they are exposed to handheld transmitters. The human brain and the mouth are modeled using the simulation program and the handheld transmitters are realized with microstrip patch antenna. The simulations depict that the dosimetry for handheld transmitters operated next to the body is below the standards.
Keywords: Radio frequency radiation; specific absorption rate; electromagnetic exposure; handheld transmitters; HUMAN HEAD; ABSORPTION RATE; MOBILE PHONE; COMPUTATION; INCREASE; ANTENNAS; RISE; MHZ